Chocolates artesanales e identidad territorial en retroalimentación con el destino Bariloche, Argentina - Colino, Evelyn del Valle (2020)
Associated with the rigorous weather of the Patagonian region and with the assistance of European immigrants, artisanal chocolate has become a symbol of Bariloche, the well-known international tourist destination of Argentina. Its production is a tradition transmitted from generation to generation. Today, Bariloche brand is a seal of quality, exclusivity and holds an image associated with the landscape beauties of the environment and even a lifestyle. Local culinary traditions are well recognized, but craft chocolate, -and the popularity achieved by some innovations created by a family of immigrants pioneer in this field-, is possibly the star product of the region. The process by which this product develops a strong territorial identity is particularly striking given that the Patagonian region is not a cocoa producer. However, there are no socio-economic studies on this case so far. From a territorial approach, this research emphasizes the chocolate-territory linkage and the association of this product to the regional tourist system. Based on the first survey carried on in this sector, the production system of Bariloche's artisanal chocolate is analyzed. Its evolution associated with the history of the place, strong profile and the marked heterogeneity between producers, innovation, expansion strategies, main opportunities, restrictions to enhance its competitive and comparative advantages in a globalized market with new demands and preferences.